AB0030 The LP13.3 genomic region -RS599839- is associated with endothelial dysfunction in patients with rheumatoid arthritis. (23rd January 2014) - Lόpez-Mejías, R.; González-Juanatey, C.; García-Bermúdez, M.; Castañeda, S.; Miranda-Filloy, J.A.; Blanco, R.; Llorca, J.; Martín, J.; González-Gay, M.A.
Abstract : Background: Rheumatoid arthritis (RA) is a complex polygenic autoimmune inflammatory disease with high risk of cardiovascular (CV) complications as consequence of accelerated atherosclerosis [1]. Recent studies have emphasized the relevance of several genetic polymorphisms in the susceptibility to CV disease in RA [2, 3]. Genome-wide association studies (GWAS) revealed that the polymorphism rs599839 (A>G) is associated with CAD [4]and with higher plasma total and LDL cholesterol levels [5]. Objectives: Wwe aimed to determine, for first time, the potential role of rs599839 polymorphism in the development of endothelial dysfunction in a cohort of RA patients without clinically evident CV disease. Methods: 128 RA patients without history of CV events were genotyped for rs599839 A/G polymorphism. Presence of endothelial dysfunction was assessed by brachial ultrasonography (brachial flow-mediated endothelium-dependent [FMD]). Results: Patients carrying the allele G exhibited more severe endothelial dysfunction (FMD%: 4.61±3.94%) than those carrying the wild allele A (FMD%: 6.01±5.15%) (p=0.08). Adjustment for gender, age at the time of study, follow-up time and classic CV risk factors disclosed a significant association between the rs599839 polymorphism and FMD (G vs. A: p=0.0062). Conclusions: Our results confirm an association of the rs599839 polymorphism with endothelial dysfunction in RA. This study was supported by two grants from "Fondo de Investigaciones Sanitarias" PI06-0024 and PI09/007/48 (Spain) and partially supported by RETICS Program, RD08/0075 (RIER) from ``Instituto de Salud Carlos III'' (ISCIII). References: Chung CP, Oeser A, Raggi P, Gebretsadik T, Shintani AK, Sokka T, Pincus T, Avalos I, Stein CM. Increased coronary-artery atherosclerosis in rheumatoid arthritis: relationship to disease duration and cardiovascular risk factors. Arthritis Rheum. 2005;52:3045-3053. Gonzalez-Gay MA, Gonzalez-Juanatey C, Lopez-Diaz MJ, Pineiro A, Garcia-Porrua C, Miranda-Filloy JA, Ollier WE, Martin J, Llorca J. HLA-DRB1 and persistent chronic inflammation contribute to cardiovascular events and cardiovascular mortality in patients with rheumatoid arthritis. Arthritis Rheum. 2007;57:125-132. Rodriguez-Rodriguez L, Gonzalez-Juanatey C, Palomino-Morales R, Vazquez-Rodriguez TR, Miranda-Filloy JA, Fernandez-Gutierrez B, Llorca J, Martin J, Gonzalez-Gay MA. TNFA -308 (rs1800629) polymorphism is associated with a higher risk of cardiovascular disease in patients with rheumatoid arthritis. Atherosclerosis 2011;216:125-30. Samani NJ, Erdmann J, Hall AS, Hengstenberg C, Mangino M, Mayer B, Dixon RJ, Meitinger T, Braund P, Wichmann HE et al. Genomewide association analysis of coronary artery disease. N Engl J Med. 2007;357:443-453. Kathiresan S, Melander O, Guiducci C, Surti A, Burtt NP, Rieder MJ, Cooper GM, Roos C, Voight BF, Havulinna AS et al. Six new loci associated with blood low-density lipoprotein cholesterol, high-density lipoprotein cholesterol or triglycerides in humans. Nat Genet. 2008;40:189-197. Disclosure of Interest: None Declared